Manipulating the molecular conformation of a nanometer-thick environmentally friendly coating to control the surface energy. Issue 20 (5th May 2017) - Kozbial, Andrew; Guan, Wei; Li, Lei
Abstract : Thermal annealing makes the environmentally friendly side-chain fluorocarbons have desired low surface energy. Abstract : Long-chain fluorocarbons are the state-of-the-art materials as nanometer-thick coatings in growing nanotechnology industries. The low surface energy, resulting from the molecular nature of C–F bonds, is the key feature of perfluoro-materials that no other material can provide. However, research in the past decades has shown that long-chain fluorocarbons pose serious toxicological and environmental concerns because their degradation products, which have at least six fluorocarbons, are bioaccumulative, toxic and have high global warming potential. One possible solution for the dilemma is to develop hydrocarbons with short fluorocarbon side chains (HC-SFSCs), which have been demonstrated to be much more environmentally friendly. However, there have been few experimental studies on nanometer-thick HC-SFSCs on a solid substrate. Moreover, it is very challenging for HC-SFSCs to provide surface energy as low as fluorocarbons do. In the current paper, a nanometer-thick HC-SFSC has been deposited on a silica substrate by dip-coating. Ellipsometry and X-ray photoelectron spectroscopy (XPS) results indicated that the as-coated HC-SFSC molecules take a conformation between "random coil" and "flat chain". Contact angle testing results showed that the as-coated HC-SFSC/silica has a relatively high surface energy and, interestingly, simple thermal annealing reduces the surface energy to a value close to that of Teflon. XPS studies suggested that the thermodynamic equilibrium conformation of HC-SFSCs on a solid substrate is actually in favor of low surface energy and the low mobility of HC-SFSCs induced by the solid confinement traps the molecule in a non-equilibrium conformation with higher surface energy. The finding here potentially provides a viable approach to make the surface energy of HC-SFSCs as low as those of the conventional perfluoro-materials.